Review on some cereal and legume based composite biscuits - Milkesa Feyera (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The major determinants of malnutrition in Africa are low availability of nutritious foods and inadequate consumption of protein-rich diets. Consumption of nutritious snacks could help to reduce protein-energy malnutrition in children and adults. Biscuits are a ready-to-eat, convenient and cheap snack that is consumed by all age group in many countries. It can be produced from cereal and legume flour blends. A proximate composition such as protein, ash, crude fiber, and fat content of some cereal-legume based biscuit increased with increase in the percentage substitution of legumes flour. Carbohydrate content of biscuits decreased as legume substitution increased. The Ash (total mineral) content of some cereal and legume-based composite biscuits increased as the level of legume flour incorporation increased. The increased in some nutrient composition of the biscuit in cereal and legume blends could be due to the significant quantity of nutrients in legumes. Anti-nutritional factors (ANF) such as tannin and phytic acid affect digestibility and nutrient bioavailability for absorption. Substitution of malted cereal flour with legume flour resulted decreased in the level of both tannin and phytate in the composite biscuits and vice versa. Lower tannin and phytate content observed could be due to degradation of tannin and phytate during malting. Sensory attributes such as color, texture, aroma, taste, and overall acceptability of some cereal and legume-based biscuits were highly rated (in acceptable ranges).